2009
DOI: 10.1073/pnas.0907795106
|View full text |Cite
|
Sign up to set email alerts
|

Thickness–radius relationship and spring constants of cholesterol helical ribbons

Abstract: Using quantitative phase microscopy, we have discovered a quadratic relationship between the radius R and the thickness t of helical ribbons that form spontaneously in multicomponent cholesterol-surfactant mixtures. These helical ribbons may serve as mesoscopic springs to measure or to exert forces on nanoscale biological objects. The spring constants of these helices depend on their submicroscopic thickness. The quadratic relationship (R ؔ t 2 ) between radius and thickness is a consequence of the crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Zastavker et al., who have experimented with diverse helix forming systems based on the crystallization of cholesterol in bile, found it unlikely that all of these systems, involving diverse molecular species, would have precisely the same two angles of molecular packing and consequently sought other explanations. Indeed, researchers in investigating the crystallization of cholesterol tend to believe that the helical assemblies that they work on are distinct from the others discussed in this Review and provide good evidence to this effect. , …”
Section: Theory Of the Self-assembly Of Amphiphiles Into Helically Ba...mentioning
confidence: 94%
See 2 more Smart Citations
“…Zastavker et al., who have experimented with diverse helix forming systems based on the crystallization of cholesterol in bile, found it unlikely that all of these systems, involving diverse molecular species, would have precisely the same two angles of molecular packing and consequently sought other explanations. Indeed, researchers in investigating the crystallization of cholesterol tend to believe that the helical assemblies that they work on are distinct from the others discussed in this Review and provide good evidence to this effect. , …”
Section: Theory Of the Self-assembly Of Amphiphiles Into Helically Ba...mentioning
confidence: 94%
“…It seems that crystallinity has often been used to describe the phase of tubules, and crystallization as the tubule forming process, simply for want of better terms to characterize the prevailing high degree of order. Nevertheless, some researchers argue that the tubule phase is crystalline. , Evidence to support this argument includes X-ray and electron diffraction studies on diacetylenic lipid tubules, which have shown chain packing with crystalline character over the length scales probed by these techniques. Such experiments have so far produced insufficient resolution to examine the extent of the correlation length, and the large number of higher harmonics is only really indicative of a highly defined lamellar order. , Part of the argument for the crystalline nature of tubes is based on the X-ray diffraction (XRD) analysis of dried tube samples, where it has been suggested that the hydration of the bilayer does not significantly affect lipid packing, although this is a dangerous assumption to make . Indeed, Thomas et al found that dry tubes showed 3-D crystallinity, while a suspension in a water/ethanol solution had no evident interlayer correlations.…”
Section: Theory Of the Self-assembly Of Amphiphiles Into Helically Ba...mentioning
confidence: 99%
See 1 more Smart Citation
“…The quadratic relationship (R f t 2 ) between radius and thickness is a consequence of the crystal structure of the ribbons and enables the determination of the spring constant of any helices solely in terms of its observable geometrical dimensions. 111 Choi et al used high-speed synthetic aperture microscopy to image helical cholesterol ribbons in surfactant mixtures, as well as to measure the thickness of a nanoscale cholesterol helical ribbon ( Fig. 3b) which was determined to be 68 nm.…”
Section: Random or Statistical Copolymersmentioning
confidence: 99%
“…Many applications of the quantitatively recorded phase information have been reported in studying biological specimens [1,2]. For samples with a homogeneous refractive index, quantified phase information can be used to determine the height of samples with nanometer accuracy [3]. Another important use of phase information is that it enables high-speed three-dimensional (3D) imaging of a sample without scanning an objective lens via numerical propagation along the axial direction [4].…”
mentioning
confidence: 99%